2019
DOI: 10.1177/1753425919862354
|View full text |Cite
|
Sign up to set email alerts
|

Associations between genetic polymorphisms of TLRs and susceptibility to tuberculosis: A meta-analysis

Abstract: Some genetic association studies have tried to investigate potential associations between TLR polymorphisms and tuberculosis. However, the results of these studies have not been consistent. Thus, we performed the present meta-analysis to explore associations between TLR polymorphisms and tuberculosis in a larger combined population. A systematic literature research of PubMed, Web of Science and Embase was performed to identify eligible studies for combined analyses. I2 statistics were employed to assess betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 21 publications
2
15
0
1
Order By: Relevance
“…However, a meta-analysis of 16 related studies by L. Zhao et al (2015) did not find that the TLR4 rs4986790 polymorphism was significantly associated with the risk of pulmonary tuberculosis. Studies have also confirmed that rs4986790 gene polymorphism is closely related to the risk of tuberculosis infection and tuberculosis progression (Thada et al, 2013;Zhou & Zhang, 2020). In the present study, we found that the frequency of G allele of TLR4 rs4986790 in the case group was higher than that of the control group.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, a meta-analysis of 16 related studies by L. Zhao et al (2015) did not find that the TLR4 rs4986790 polymorphism was significantly associated with the risk of pulmonary tuberculosis. Studies have also confirmed that rs4986790 gene polymorphism is closely related to the risk of tuberculosis infection and tuberculosis progression (Thada et al, 2013;Zhou & Zhang, 2020). In the present study, we found that the frequency of G allele of TLR4 rs4986790 in the case group was higher than that of the control group.…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, there is no significant correlation between IFNGR1 rs1327474 and the risk/protection of pulmonary tuberculosis (Naderi et al, 2015). The research results of the relationship between the rs4986790 gene polymorphism in TLR4 and tuberculosis are inconsistent in different populations (Ortega et al, 2020;Thada et al, 2013;Zhou & Zhang, 2020;L. Zhao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…genetic traits). 37 , 38 , 39 This inference is supported by the association of self-reported ethnicity with incident TB, although mixed ancestry may be a proxy variable for the Western Cape Province sites (Worcester and Ravensmead), where people of mixed ancestry comprise a large proportion of the population. 40 Local transmission dynamics are likely responsible for site level differences in Mtb sensitisation.…”
Section: Discussionmentioning
confidence: 94%
“…The main eHsp70 receptors TLR2 and TLR4 are activated mostly by pathogen components but can also be activated by proteins released from dying cells, including Hsps that act like DAMPs. Activation of the TLR signaling pathway leads to the production of proinflammatory cytokines [32]. Overall, available data on TLR2 and TLR4 expression are conflicting, and results seem to be by cell type i.e., tissue specific.…”
Section: Discussionmentioning
confidence: 99%
“…The C/C carriers of the HSP70 rs1043618 were associated with an increased risk of lung cancer [39], and with higher risk of coronary heart disease, while reduced expression of Hsp70 protein was affected by the polymorphism [21]. TLR2 and TLR4 polymorphisms were associated with various conditions such as asthma [40], pulmonary tuberculosis [32,41], Helicobacter pylori infection [42], as well as alterations in levels of high-density lipoprotein cholesterol, low-density lipoprotein cholesterol and triglycerides [36]. They were also associated with susceptibility to COPD [25], the level and decline of lung function, an increased number of inflammatory cells in induced sputum of COPD patients [24], and an increased risk of COPD in smokers [43] or an earlier stage of COPD [44].…”
Section: Discussionmentioning
confidence: 99%